If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(z + -3) = 6z Reorder the terms: 7(-3 + z) = 6z (-3 * 7 + z * 7) = 6z (-21 + 7z) = 6z Solving -21 + 7z = 6z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-6z' to each side of the equation. -21 + 7z + -6z = 6z + -6z Combine like terms: 7z + -6z = 1z -21 + 1z = 6z + -6z Combine like terms: 6z + -6z = 0 -21 + 1z = 0 Add '21' to each side of the equation. -21 + 21 + 1z = 0 + 21 Combine like terms: -21 + 21 = 0 0 + 1z = 0 + 21 1z = 0 + 21 Combine like terms: 0 + 21 = 21 1z = 21 Divide each side by '1'. z = 21 Simplifying z = 21
| 2x-6=8x+14 | | 3x(2x)=90 | | 7*51+-0.67b+5b= | | 1/3(x-2)=1/3 | | -56+11x=40+3x | | 7(-2)-4y=10 | | -c=25 | | 10=5(x-3) | | -4(x-2)=4(3-2x) | | 0=-15t^2-18t+12 | | 4-12a-15=35-20a | | 9a+6b=459 | | x(1+x)=x^2-3+8 | | (4x+12)+(6x+8)=90 | | -4w-6(-7x+5w)+2w= | | (8+3i)-(8-3i)= | | 6x+6(3)y=70 | | 6x+6(3)y=64 | | 7(x+3)+9-2x=4(x+5)+.5(2x)+28 | | -5(10)-2y=24 | | 0=y^2+10y+25 | | 1z-16=14z-68 | | 7+33=-4(2x-10) | | X+5-x=4x-1-x | | 2(5)-8y=10 | | 7+-2t=-56+5t | | -3(x-1)=-4x+6 | | 3(5c-1)-1=12c+2 | | Y=x(x)-7 | | 3-49=7 | | 10x+9y+8z=175 | | -3(-5)+10x=-5 |